2014
DOI: 10.1007/s10853-014-8467-x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide adsorption using amine-functionalized mesocellular siliceous foams

Abstract: Mesocellular siliceous foams (MCFs) with and without remaining template were prepared and modified by polyethylenimine (PEI) or mixed amines [Diethylenetriamine and PEI or 3-aminopropyltrimethoxysilane (APTMS) and PEI]. These samples were evaluated for their adsorption capacities for CO 2 at different temperatures. With the increase of PEI loading, the optimal adsorption temperature shifts to higher temperature for samples prepared in our study. The remaining template in MCF materials plays an important role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The results obtained for 30 and 40 wt % loadings are consistent with the data reported by Heydari-Gorji et al The sorbent with 50 wt % loading cannot be compared with their observations because they did not present a sorbent with completely filled pores. The study of Ma et al has such a sorbent (i.e., MCF­(c)/PEI-70); however, their findings show a higher effect of temperature on the sorbent’s capacity, likely due to a longer exposure time to CO 2 .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The results obtained for 30 and 40 wt % loadings are consistent with the data reported by Heydari-Gorji et al The sorbent with 50 wt % loading cannot be compared with their observations because they did not present a sorbent with completely filled pores. The study of Ma et al has such a sorbent (i.e., MCF­(c)/PEI-70); however, their findings show a higher effect of temperature on the sorbent’s capacity, likely due to a longer exposure time to CO 2 .…”
Section: Resultsmentioning
confidence: 95%
“…Zhao et al studied the thermal stability of TEPA at 140 °C using a fluidized bed and found that entrained amine vapor can effectively impede TEPA’s diffusion from the porous medium, which may also occur in overloaded sorbents with a polymer layer coating the external surface. Nevertheless, increasing polymer loading requires higher adsorption temperatures to facilitate CO 2 diffusion, , which also applies to the reverse step . Indeed, sorbents with high polymer loading can offer high adsorption capacity; however, this comes at the cost of requiring high desorption temperatures and times, which can significantly affect the sorbent’s stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have explored the role of additives in carbon capture, and most of them were performed under post-combustion conditions. 364–369 Accordingly, the main types of effective additives are surfactants (poly(ethylene glycol) (PEG), 300,370–373 glycerol, cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC), Pluronic P123, and sorbitan monooleate (Span80), silanes, 374,375 sulfur-containing compounds, antioxidants, 376 ionic liquids, 377 and potassium carbonate. 378 PEG has been investigated most frequently and showed positive effects on adsorption properties, possibly because of its rich hydroxyl groups that can facilitate better amine dispersion and attract more water molecules.…”
Section: Synergetic Enhancement Between Amines and Supportsmentioning
confidence: 99%
“…By modification of PEI, the application range can be further expanded. Amidation with acids, alkoxylation, alkylation and carboxylation has been performed, leading to PEI-modified structures used as CO 2 cells [123,124], detectors with specific recognition elements [125,126], drug delivery [127] or nano-carriers [128], among others.…”
Section: Hbps and Multiarm Sps From Peimentioning
confidence: 99%